Pemberdayaan Masyarakat Melalui Produk Olahan Jagung Manis (Zea mays L. Saccharata Sturt) Menjadi Stik Jagung Balado Desa Bontula Gorontalo - Ernikawati, Ernikawati; Puspaningrum, Dian; Ibrahim, Yulianti; Akase, Lisna (Universitas Gorontalo, 2025)
Community empowerment can be achieved by maximizing potential that can be managed effectively. Bontula Village is one of the villages in Asparaga District, Gorontalo Regency, and the most prominent product is corn. Because only raw corn plants are sold in the market, the yield of each plant is less than optimal in providing income for village residents. Based on the problems mentioned above, it is necessary to empower the Bontula village community to improve the economic welfare of its population by developing processed products available in the area. Apart from that, the aim of this activity is to increase the knowledge and economy (income) of the community through utilizing existing resources in the area. The use of corn-based sticks by adding balado flavor variants is oriented not only to maximizing the use of corn, but also focuses on increasing the income of village residents. This activity is carried out in stages, starting with observation, socialization, mentoring, packaging, and ending with marketing trials. After some trial marketing, corn chips were offered at nearby kiosks/stores and markets. Overall, there is a positive response from customers. This is proven by the existence of reorders made by the market. Community empowerment is very important because apart from increasing community knowledge and awareness about the use of natural resources, this activity also helps increase the level of village participation. Keywords : Community empowerment; Corn sticks; Bontula Village.